Midwifery and Sexuality - Geuens, Sam; Polona Mivšek, Ana; Gianotten, Woet.L (Springer International Publishing : Imprint: Springer, 2023)
This first open-access book on midwifery and sexuality integrates sexual health into the care for the pregnant and postpartum couple. It addresses sexuality and intimacy from an education and prevention perspective instead of just focusing on treating problems, aiming to foster the development of sexual well-being and happy couplehood. Sexuality and intimacy are essential elements in the bonding of the couple and the parents-to-be. That process can be seriously hampered by sexual problems due to mutual misunderstanding, fear and sexual troubles (especially when the natural processes of conceiving, pregnancy and delivery are disturbed). In this phase of life, disruption of intimacy, sexuality and sexual relationship is a significant risk factor for developing couple and family problems. The need for such a book stems from the very limited attention given to this health area in the daily practice of most midwives and related healthcare professionals. In building a close relationship with the couple through frequent, intense, longstanding contact, the midwife acquires a perfect position to address sexuality and intimacy. With 36 authors from 14 countries, the book comprises five modules: 1. Sexuality; 2. Sexual aspects of the various phases of reproduction when things develop without complications; 3. Sexual aspects when those same phases deviate from physiology; 4. Special topics on sexuality relevant to daily midwifery practice; 5. Teaching, learning, skills and competencies with regard to sexuality. This new practical textbook guides healthcare professionals such as midwives, obstetricians, gynaecologists, nurses, general practitioners, pelvic floor therapists, etc., by offering both basic knowledge and skills on sexual health and wellbeing, combined with modern sexological knowledge, like the entirely new topic of sexual aspects of preconception care. This is an open access book.